Mitigating phosphoric acid leaching in high-temperature proton exchange membrane fuel cells through microporous layer engineering - Oh, Kangmin; Kang, Hyun Woo; Kim, Gayoung; Cho, Jaewoo; Kim, Daeho; Cho, Jaehyun; Lee, So Young; Park, Chi Hoon; Park, Sehkyu (Elsevier BV, 2026)
Phosphoric acid (PA) leaching is a critical issue affecting the performance and durability of high-temperature proton exchange membrane fuel cells (HT-PEMFCs). This study presents a novel microporous layer (MPL) that is designed to effectively reduce PA discharge from the cathode catalyst layer (CL). Carbon slurries with various ethyl cellulose (EC) contents are prepared as the polytetrafluoroethylene (PTFE) dispersants and pore formers, and their dispersion behavior is analyzed using an optical analyzer and mesoscale molecular simulations. Inhouse-fabricated gas diffusion layers (GDLs) with optimized carbon slurries and commercial GDLs are evaluated through ex situ and in situ characterization. The results indicate that EC facilitates uniform PTFE distribution and inhibits the formation of large cracks on the MPL surface while promoting mesopore generation in the MPL through its thermal decomposition. Consequently, the optimized MPL structure effectively retards PA release from the cathode CL during extended HT-PEMFC operation, enhancing both cell performance and stability.